Response to lenvatinib and pembrolizumab combination therapy in pembrolizumab-pretreated relapsed endometrial cancer - Kaito Mimura; Akihiko Shimomura; Tomoko Gota; Kenju Ando; Yukino Kawamura; Tomoko Taniyama; Hajime Oishi; Chikako Shimizu (Elsevier, 2022)
Uterine endometrial cancer is one of the most common gynecological malignancies worldwide. With relatively few options for late-line therapies for advanced or relapsed endometrial cancer, the use of pretreated therapies may broaden the choice of treatments. Here, we report a case of recurrent microsatellite instability-high endometrial cancer that acquired resistance to pembrolizumab but favorably responded to the lenvatinib and pembrolizumab combination therapy. Lenvatinib combined with pembrolizumab may be effective against endometrial cancer resistant to pembrolizumab monotherapy, encouraging its use regardless of prior administration of immune checkpoint inhibitors. Further investigation on the lenvatinib and pembrolizumab combination therapy and the mechanism underlying its anticancer effect may provide new insights into cancer immunotherapy and tumor microenvironments.